Study the utilization of waste water from the coagulation of raw rubber sheet for rubber cup lump coagulation - วัดจัง, ชัยวุฒิ; บุญยอด, เสาวลักษณ์; กาญจนา, ประสิทธิ (Progress in Applied Science and Technology, 2018)
This research aimed to study the utilization of waste water from the coagulation of raw rubber sheet in rubber cup lump coagulation. The acidity levels of waste water are low for use as the coagulating agent into rubber cup lump. The quality amount of waste water and the mixing ratio between formic acid/wastewater were studied to compare properties of rubber cup lumps from the coagulation of waste water with formic acid. The study found that the wastewater can coagulate rubber cup lumps best waste water content at 50 ml to coagulation a rubber cup lump for 5 h. The ratio of formic acid/waste water to coagulate rubber cup lumps as quickly and completely as possible was 50:50, the amount of formic acid/waste water volume of 15-30 ml that can coagulate rubber cup lumps for 35 minutes. The color of the rubber cup lump had a light brown color, similar to the rubber cup lump coagulation with formic acid. Moreover, the properties of rubber cup lump coagulation by formic acid/wastewater are the same properties as the Standard Thai Rubber from rubber cup lump coagulation with formic acid.